2017
DOI: 10.1371/journal.ppat.1006250
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced control of Mycobacterium tuberculosis extrapulmonary dissemination in mice by an arabinomannan-protein conjugate vaccine

Abstract: Currently there are a dozen or so of new vaccine candidates in clinical trials for prevention of tuberculosis (TB) and each formulation attempts to elicit protection by enhancement of cell-mediated immunity (CMI). In contrast, most approved vaccines against other bacterial pathogens are believed to mediate protection by eliciting antibody responses. However, it has been difficult to apply this formula to TB because of the difficulty in reliably eliciting protective antibodies. Here, we developed capsular polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 66 publications
2
92
0
Order By: Relevance
“…Another way antibodies can dampen inflammation is via direct microbial effects. Antibodies to bacteria, mycobacteria, and fungi that alter microbial transcription, metabolism, or growth have been described [48][49][50][51] and may hold promise as therapeutic agents.…”
Section: A Damage-response Framework-informed Approach To Combating Imentioning
confidence: 99%
“…Another way antibodies can dampen inflammation is via direct microbial effects. Antibodies to bacteria, mycobacteria, and fungi that alter microbial transcription, metabolism, or growth have been described [48][49][50][51] and may hold promise as therapeutic agents.…”
Section: A Damage-response Framework-informed Approach To Combating Imentioning
confidence: 99%
“…Elevated AM‐specific immunoglobulin G (IgG) titers in BCG‐vaccinated healthy donors correlated with improved mycobacterial opsonophagocytosis and intracellular growth inhibition in human macrophages . In murine Mtb challenge models, AM‐protein conjugate vaccines extended the survival time of animals . Antibodies against cell wall‐associated glycolipid lipoarabinomannan, which structurally overlaps with AM, could contribute to containment of M. tuberculosis infection in children.…”
Section: The Role Of Antigen Specificity Of Antibodies In Tbmentioning
confidence: 99%
“…41 In murine Mtb challenge models, AM-protein conjugate vaccines extended the survival time of animals. 45,46 Antibodies against cell wall-associated glycolipid lipoarabinomannan, which structurally overlaps with AM, could contribute to containment of M. tuberculosis infection in children. The lack of lipoarabinomannanspecific antibodies in children with TB disease predisposed them to disseminated TB.…”
Section: The Role Of Antigen Specificity Of Antibodies In Tbmentioning
confidence: 99%
“…Moreover, in vitro and animal studies using antibodies to M. tuberculosis antigens have shown enhanced protection with increased survival and reduced bacterial burden (77,78). Recent immunization studies with mycobacterial capsular arabinomannan conjugates have demonstrated antibody and T cell responses that contribute to protective immunity against M. tuberculosis (79). These findings provide evidence for the potential role of humoral immunity in TB vaccine development strategies.…”
Section: Humoral Immunity By B Cellsmentioning
confidence: 99%